2015
DOI: 10.1017/s1366728915000322
|View full text |Cite
|
Sign up to set email alerts
|

Effects and noneffects of input in bilingual environments on dual language skills in 2 ½-year-olds

Abstract: Recent findings suggest some properties of input in dual-language environments that influence its value for bilingual development, but the extant data base is small and sometimes inconclusive. The present study sought additional evidence regarding three quality indicators: the percent of input provided by native speakers, the number of different speakers providing input, and the frequency of language mixing. Participants were 90 thirty-month-olds exposed to Spanish and English. Using the Language Diary method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
131
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(150 citation statements)
references
References 39 publications
15
131
4
Order By: Relevance
“…In a sample of 25-month-olds, which included some of the children from bilingual homes in the current sample, the portion of children’s input that was provided by native English speakers was a unique predictor of the children’s English vocabulary (Place & Hoff, 2011), and that finding was replicated in a separate sample of 30 month-olds (Place & Hoff, 2013). Two separate studies, one of 4- to 7-year-old immigrant children and a second of preschool children in immigrant families in English-speaking Canada, found no relation between children’s English exposure at home and their English skills (Paradis, 2011; Paradis & Kirova, in press).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In a sample of 25-month-olds, which included some of the children from bilingual homes in the current sample, the portion of children’s input that was provided by native English speakers was a unique predictor of the children’s English vocabulary (Place & Hoff, 2011), and that finding was replicated in a separate sample of 30 month-olds (Place & Hoff, 2013). Two separate studies, one of 4- to 7-year-old immigrant children and a second of preschool children in immigrant families in English-speaking Canada, found no relation between children’s English exposure at home and their English skills (Paradis, 2011; Paradis & Kirova, in press).…”
Section: Discussionmentioning
confidence: 70%
“…The EOWPVT was administered to the children from bilingual homes by a trained bilingual examiner in English and Spanish, on separate days in counterbalanced order. The validity of the EOWPVT as we have administered it and its comparability to the CDI as an index of expressive vocabulary is supported by findings that the two measures were highly correlated in a different sample of monolingual and bilingual 30-month-olds who were administered both instruments as part of another ongoing project in our lab ( r [153] = .80, p < .001; Place & Hoff, 2013). …”
Section: Methodsmentioning
confidence: 72%
“…The linear effect of Spanish exposure is consistent with the finding from another study of this sample that virtually all the children’s Spanish exposure came from native Spanish speakers. 18 Overall, expressive Spanish skills in these bilingual children were low and growing at a slower rate than English skills. This likely reflects that exposure to English was greater outside the home and also that the children chose to speak English more than they chose to speak Spanish.…”
Section: Discussionmentioning
confidence: 90%
“…Children’s language skills were assessed at the ages of 30, 36, 42, 48, 54, and 60 months as part of a larger study of bilingual development. 18,19 The attrition rate for the larger study during the period from 30 to 60 months was 17.5%. There were additional missing data for some participants at each assessment point.…”
Section: Methodsmentioning
confidence: 95%
“…Previous studies using measures of parent report have suggested that language mixing affects children's vocabulary differently in different populations(Bail et al, 2015;Byers- Heinlein, 2013;Place & Hoff, 2016). However, when toddlers heard sentence frames in their non-dominant language, they successfully recognized target nouns in both languages.…”
mentioning
confidence: 89%